THE EFFECT OF COMPARISON OF CONCRETE USING TANGKILING SAND AND KAPUAS SAND ON THE COMPRESSIVE STRENGTH OF CONCRETE - Whendy Trissan; Yongki Pratomo (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2020)
In general, concrete fillers are made from materials that are easily obtained, easily processed, and have the durability and strength that is very much needed in particular construction of coarse and fine aggregates, each region would have different aggregates as the main ingredients in making concrete. The research conducted aims to determine how the optimum compressive strength value of the concrete produced from the addition of Kapuas Sand to the concrete mixture. In this research, Kapuas Sand is used as a fine aggregate enhancer. The percentage variation of Kapuas red sand used in this study varies, namely 0%, 25%, 50%, 75%, and 100%. Concrete mixture planning using SNI 03-2834-2000. The test uses cylindrical specimens with a height of 30 cm, a diameter of 15 cm with a total sample of 10 cylinders for each addition of Kapuas Sand so that the total specimens are 50 cylinders. Testing is carried out at the age of 14 and 28 days in the Laboratory of Building Engineering Education Study Program, Faculty of Teacher Training and Education, University of Palangka Raya. The results of the compressive strength of concrete using a mixture of Kapuas Sand at 28 days 0% 25%, 50%, 75% and, 100% respectively were 24.71 MPa, 21.79 MPa, 25.36 MPa, 23 .3 MPa, and .22.62 MPa. This result shows the compressive strength value of concrete in the concrete mix with a percentage of 50% that is equal to 25.36 MPa while the compressive strength of normal concrete is 24.71 MPa so that the compressive strength of concrete is 2.66% of normal concrete compressive strength with age concrete compressive strength 28 days.